Enhancing Management Students’ Competencies through Digital Learning Innovation: The Use of Artificial Intelligence and Canva - Rahma Febrianti; Irsyadi Yani; Tri Yusnanie; Mu'izzuddin Mu'izzuddin (Biro Administrasi dan Akademik, 2026)
The rapid development of digital technology, particularly Artificial Intelligence (AI), requires students to possess adequate digital literacy competencies in the learning process. However, its utilization remains largely technical and has not been optimally integrated to enhance academic quality. This community service activity aims to improve the competencies of Management students through digital learning innovation by utilizing AI and Canva in developing academic presentation materials. The activity was implemented through training and mentoring in the form of a mini workshop, which included the introduction of AI, effective prompt construction, and hands-on practice in creating presentation materials using Canva. The program was conducted with undergraduate Management students and evaluated using questionnaires to assess participants’ understanding, skills, and satisfaction. The results indicate a significant improvement in students’ ability to systematically develop academic content using AI, as well as increased creativity in designing presentations through Canva. In addition, students demonstrated a better understanding of the ethical and responsible use of AI in academic contexts.This activity implies that the integration of AI and digital design tools can enhance learning quality, foster creativity, and strengthen students’ digital competencies. Therefore, the use of AI and Canva as digital learning innovations is effective in improving students’ academic competencies and digital literacy, while also preparing them to face the challenges of learning in the digital transformation era.